e) [tex]-7\frac{1}{5} + 3\frac{4}{7} = -\frac{36}{5} + \frac{25}{7} = -\frac{252}{35} + \frac{125}{35} = -\frac{127}{35} = -3\frac{22}{35}[/tex]
f) [tex]-2\frac{1}{7} + 5\frac{3}{4} = -\frac{15}{7} + \frac{23}{4} = -\frac{60}{28} + \frac{161}{28} = \frac{101}{28} = 3\frac{17}{28}[/tex]
g) [tex]-3\frac{1}{7} - 2\frac{3}{4} = -\frac{22}{7} - \frac{11}{4} = -\frac{88}{28} - \frac{77}{28} = -\frac{165}{28} = -5\frac{25}{28}[/tex]
h) [tex]-2\frac{1}{3} + \frac{7}{8} = -\frac{7}{3} + \frac{7}{8} = -\frac{56}{24} + \frac{21}{24} = -\frac{35}{24} = -1\frac{11}{24}[/tex]
i) [tex]0,7 - 1,3 = -0,6[/tex]
j) [tex]-2,4 + 5,1 = 2,7[/tex]